Facile Biodiesel Synthesis from Esterification of Free Fatty Acids Catalyzed by SO3H-Functionalized Ionic Liquid - Zhou, Shuai; Liu, Lu; Wang, Bo; Xu, Feng; Sun, Runcang (Asian Journal of Chemistry, 2012)
The esterifications of free fatty acids with methanol were efficiently accomplished over a SO3H-functionalized ionic liquid, 1-(4-sulphonic acid)butyl-3-methylimidazolium hydrogen sulphate ([BSMim]HSO4), which are commonly considered as both one of the typical synthetic routes and the representative pretreatment process for biodiesel production. Particularly, the maximum yield of methyl oleate was obtained in 99.9 %. Methyl oleate could be isolated through simple decantation from the biphasic system, which is attributed to the immiscibility of [BSMim]HSO4 with hydrophobic ester and the good stability and operability of ionic liquid were demonstrated by the six times reuses without dramatic decrease in methyl oleate yield.